Effectiveness of the cool-critical-creative-meaningful (3CM) learning model on enhancing students' critical thinking skills - Kintoko, Kintoko; Hadi Siswanto, Deny (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
This study aims to examine the effectiveness of the Cool Critical Creative Meaningful (3CM) learning model on the critical thinking skills of Grade X-A students at SMA Muhammadiyah 1 Sleman. The model is expected to promote meaningful learning and enhance students' higher-order thinking skills. This research employs a quantitative approach using a Pre-Experimental Design with a One-Group Pretest-Posttest type. The sample consisted of 28 students from class X-A. The instrument used was a critical thinking test developed based on the indicators of Focus, Reason, Inferences, Situation, Clarity, and Overview, and had been tested for validity and reliability. Pretest and posttest results were analyzed using normality tests, Paired Sample T-Test, and N-gain analysis. The findings show a significant improvement in students' critical thinking skills following the implementation of the 3CM model, with the average score increasing from 55.16 to 87.30 and an N-gain score of 0.72 (high category). All critical thinking indicators showed improvement, with the "Situation" indicator showing the highest increase. These results indicate that the 3CM learning model is effective in enhancing students' critical thinking skills and can serve as a reference in the development of innovative learning strategies and curriculum evaluation at the senior high school level.